A Systematic Review: Student Focus on Online Learning Trends in Indonesia 2015-2020 - Dwi Sulisworo, Dian Artha Kusumaningtyas, Trikinasih Handayani (International Journal of Advanced Science and Technology, 2020)
In 2020, Indonesia, through MOEC, has declared the utilization of online learning as one of the critical factors in the process of modern education transformation. This study aimed to review the research development related to online learning in Indonesia to realize the potentials of online learning in improving the quality of education. The study focus on online learning chosen is those emphasizing the student’s side. With data and information in this study, educators, policymakers, and researchers can make plans, predictions, and agendas of the policies that support the utilization of online learning for the development of education. The systematic review was conducted using secondary data taken from the Scopus database. The documents were filtered gradually to obtain a more comprehensive and in-depth study. Particularly in the higher education of educational institutions for educators and educational personnel, there are still a few studies on online learning that focus on students. However, there is optimism about the significant increase in related research from year to year. The result of the analysis can describe online learning implemented in Indonesia, particularly on the emphasis on the significance of students expected to get the most benefits from online learning. The issues related to the learning platform, outcome, learning management, teachers’ competencies, subjects, and media will continuously develop and change dynamically and quickly, along with the development of other sciences.